Biological influence of extracts of cryopreserved fragments of piglets’ heart and skin - Rohoza, L.A.; Bespalova, I.G.; Чиж, М.О.; Halchenko, S.Ye; Sandomirsky, B.P. (bioRxiv preprint first posted online Sep. 5, 2017; doi: http://dx.doi.org/10.1101/184622, 2017)
One of the new directions on which the searches used to find the methods to effectively correct the regeneration in case of different pathologies is the application of biologically active peptides and their mixtures. In the work there was investigated the biological influence of extracts of cryopreserved fragments of skin and heart of newborn piglets with the cold wound of skin and myocardial ischemia in rats respectively. For investigations the extracts were obtained from cryopreserved fragments of newborn piglets’ skin and heart. Cold wound of skin was modelled in rats by 10 mm copper applicator cooled in liquid nitrogen down to -196°С; the areas of wounds were determined by planimetric method, the white blood cells’ counts were analysed. In rats with myocardial ischemia there were studied the electrocardiograms, heart rate variability and proliferative activity of heart cells. The injection of extracts of cryopreserved fragments of skin to the animal’s abdominal cavity accelerates the healing of cold wound of skin and normalizes the response of immune system to an injury. After the injection during 2 months to the animals with myocardial ischemia with extracts of cryopreserved fragments of heart the normalization of electrophysiological indices of heart activity was observed that testified about the improved blood supply to a heart muscle. Being injected to healthy animals and those with myocardial ischemia the extracts of cryopreserved fragments of heart resulted in an increase in proliferative activity of heart cells. The studied extracts have a high biological effect and can be applied when designing the drugs for regenerative medicine.
Rohoza L.A., Bespalova I.G., Chizh M.O., Halchenko S.Ye., Sandomirsky B.P. Biological influence of extracts of cryopreserved fragments of piglets’ heart and skin // bioRxiv preprint first posted online Sep. 5, 2017; doi: http://dx.doi.org/10.1101/184622
Keywords: Cold wound; Myocardial ischemia; Peptides; Regeneration